Construction Versus Closed Analogies: Effects of Mediation and Relation to Working Memory - David Tzuriel (Pensa MultiMedia, 2022)
The goals of the current study are to examine (a) the effect of mediation of Construction Analogies versus mediation of Closed Analogies on cognitive modifiability in analogical thinking (b) the effect of mediation of analogies on working memory (WM), and (c) the correlation pattern between analogical thinking and WM in Construction and Closed analogies. A sample of Grade 1 children (49 boys and 47 girls) were randomly assigned to Construction analogies (E1, n = 48) and Closed Analogies (E2, n = 48) groups. Children in E1 group were administered the Construction version of the Analogical Modifiability Puzzle Test (AMPT) and children in E2 group were administered the Closed version. Both versions were administered in a dynamic assessment (DA) procedure which includes pre-teaching, teaching and post-teaching phases. Both groups were administered the Children's Spatial Working Memory (CSWM) test before and after the teaching phase. The findings reveal that both groups improved their analogical thinking from pre- to post-Teaching, with E1 group showing higher improvement than E2 group. Both groups showed significant pre- to post-teaching improvement in WM-- a finding that indicates far-transfer effects. Analogical thinking was significantly correlated with WM in pre-Teaching phase of Construction Analogies whereas analogical thinking was significantly correlated with WM in post-teaching phase of Closed Analogies. The findings raise questions about the cognitive factors involved measuring analogical thinking using a closed analogies format. The findings are discussed in relation to the effects of task characteristics, mediation in DA and recent research on WM.